Literature review of genes responsible for intramusculat fat content and its methodology in swine - Grünvald, Petra; Halas, Veronika; Tossenberger, János; Jócsák, Ildikó (Acta Agraria Kaposváriensis, 2020)
The organoleptic value of pork, e.g. its taste and tenderness, as well as overall acceptability is positively influenced by fat content, including both inter- and intramuscular fat (IMF) content up to a certain threshold. Recently, a number of research dealt with studying the genetic background of IMF incorporation. Many genes have been identified that are involved in fat metabolism and in development of marbling in muscle tissue. The aim of this work is to review the current literaure written about the most important genes and gene families that play role in IMF metabolism. The most studied genes are FABP3 and FABP4, which are part of the FABP family. They have a key role in the transport and intermediate metabolism of lipids. Number of studies have recently been published discussing the role of SCD (stearoyl-CoA desaturase) encoding gene in IMF content. Since multiple genes have been already identified playing a key role in fat metabolism and in fat deposition in muscle tissue, its gene expression studies are crucial in genetic programmes as well as in nutrigenomical research.
Keywords: Swine; IMF; Gene expression; SNP; GWAS